The alchemy of wolves and sheep : a relational approach to internalized perpetration in complex trauma survivors - Schwartz, Harvey L., 1955- (New York : Routledge, 2013)
"The literature on psychological trauma and traumatic attachment has progressed over the past few decades, however issues of coerced and internalized perpetration have not been fully explored and deconstructed. This book presents a synthesis of relational and archetypal psychology, trauma and dissociation theory, and highly relevant child soldier literature, to offer new clinical perspectives to assist psychotherapists and trauma patients to achieve more successful therapy outcomes. The Alchemy of Wolves and Sheep offers instructive, cautionary and innovative therapeutic approaches to help transform the lives of survivors of complex trauma. Offering an explanation of how the effects of coerced perpetration trauma are built, and the damage done to the psyches and lives of most trauma victims, the book extends our knowledge base in a thorough deconstruction of the nature of perpetration and its effects on the psyche. Chapters include: - trauma, dissociation, and coerced perpetration - the child soldier as a model of internalized perpetration - relational concepts in the treatment of trauma and dissociative disorders - treatment trajectory - archetypal constructs as a vehicle for integration. This book provides valuable new perspectives on the psychodynamic challenges and opportunities for mental health professionals treating internalized perpetration in survivors of complex trauma, and will prove essential reading for psychotherapists, psychoanalysts and post-graduate students as well as researchers, legal scholars and policy makers"--
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Psychic trauma in children -- Complications -- Treatment; Post-traumatic stress disorder in children -- Complications -- Treatment; Dissociative disorders in children -- Treatment; Child soldiers -- Social aspects; Electronic books